Hitler's lies : an answer to Hitler's Mein Kampf - Harand, Irene (Ahemedabad : Jaico Publishing House, 2013)
First published in Vienna in 1935, Hitler's Lies by Irene Harand is a challenge to the arguments, assumptions and actions of the German dictator, Adolf Hitler. The original German language version of the book was called Sein Kampf -Antwort an Hitler von Irene Harand (His Struggle -The Answer to Hitler from Irene Harand). In this book Harand explodes the myth of racial and national superiority. She deals with lies about the Jews which formed the basis for Hitler's propaganda and attacks the persecution of the Jews on the ground that Anti-Semitism debases Christianity. In her own words: The ruthless force of the Nazis has been directed against the Jewish and Catholic minorities. Their main attack, however, has been launched against German Jewry, which has had to bear unspeakable torture and humiliation in the Third Reich. They foster and unleash hatred against the Jews and commit wholesale murder to maintain a power they have wrested from others. It, therefore, lies in the interest of truth to make public answer to the Nazi Bible, Mein Kampf, (Hitler's autobiography) and to ascertain whether the main doctrines of this book, upon which the Nazi political state is founded, can bear critical examination before the civilized world. As the first publishers of Mein Kampf in India, Jaico is proud to revive Harand's work, which was largely forgotten since the 1950's in both her native Austria and her new home land America.
Keywords: Hitler, Adolf. -- 1889-1945.